IMPLEMENTASI KURIKULUM MERDEKA - Ibrahim, Ibrahim; Yulanda, Della; Mahalita, Fenda Resi; Nupus, Fiona Hayatun; Agus, Agus (UIN Imam Bonjol Padang, 2024)
This research is related to the implementation of the independent curriculum at MAN 2 Palembang. The study explores the process of implementing the independent curriculum in the madrasah. The research is qualitative with a descriptive approach. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data collection, data presentation, verification, and drawing conclusions. Based on the results and discussion, the implementation has been carried out in accordance with the regulations set by the government. In the implementation of this curriculum, several activities have been conducted, including providing an understanding of the concept of the independent curriculum to all relevant parties, organizing training for educators, developing teaching materials according to the standards of the independent curriculum, fostering collaboration and cooperation in the field of education, and utilizing technology in the teaching process. With the implementation of the independent curriculum, the classroom becomes more dynamic and responsive, meeting the individual needs of students and the requirements of the madrasah.